Waste Reduction in the Sickle Production Process Using the VALSAT Method and Value Stream Mapping - Jatmiko, Lovia Vioni Putri; Safirin, Moch. Tutuk (Golden Ratio of Data in Summary, 2025)
This research aims to minimize waste in the sickle production process at PT XYZ by applying Lean Manufacturing techniques, specifically Value Stream Mapping (VSM) and Value Stream Analysis Tools (VALSAT). The study began with direct observation and data collection of production activities to identify non-value-added activities (NNVA) and waste. Types of waste, including defects, excessive inventory, and waiting times, were identified and analyzed using the 5 Whys method to determine their root causes. Process Activity Mapping (PAM) was employed to classify activities into value-adding, non-value-adding, and necessary non-value-adding categories. Improvements were implemented, such as optimizing material transfers with forklifts, reducing waiting times, and strengthening quality control processes. As a result, non-value-adding activities were reduced from 9% to 0%, significantly enhancing production efficiency.